PENGARUH AKTIVITAS FISIK BERBASIS ALAM TERBUKA TERHADAP REGULASI EMOSI DAN GERAK MOTORIK ANAK USIA DINI - Janita, Almira; Cahniyo Wijaya Kuswanto (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
This study aims to analyze the effect of nature-based physical activities on emotional regulation and gross motor skills in early childhood. The study was motivated by findings indicating that children aged 5–6 years continue to experience difficulties with emotional control and gross motor coordination. The research was conducted at TK Aisyiyah 3, Bandar Lampung, through a 30-day intervention involving outdoor, nature-based physical activities. Data were collected through observation, the Emotion Regulation Checklist (ERC), the Test of Gross Motor Development (TGMD), and daily activity logs. The findings indicate that nature-based physical activities have a significant positive effect on improving children’s emotional regulation and gross motor skills. These results confirm that natural environments can function as effective learning media to support children’s emotional and physical development holistically.